PENGARUH INSTITUTIONAL OWNERSHIP TERHADAP FINANCIAL PERFORMANCE DENGAN INTELLECTUAL CAPITAL SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mely Trya Agustina; Josua Tarigan (Business Accounting Review, 2017)
This study aimed to prove that there was influence of institutional ownership to financial performance with intellectual capital as intervening variable. The sample used in the study consisted of 89 manufacturing companies listed in Indonesia Stock Exchange with observation year during 2011-2015. This study used data collected from annual reports and financial reports, then data processed byusing WarpPLS software version 5.0.The results of this study proved that the higher institutional ownership would increase intellectual capital, because institutional investors had a goal to increase long-term incentives for the companies. With the manage and the use of intellectual capital effective and efficient would improve the company's ability to improve financial performance. This was evidenced by the positive influence of institutional ownership on intellectual capital, positive influence of institutional ownership on financial performance, and positive influence of Intellectual Capital on financial performance.